Effects of Oral Iron Supplementation on Blood Iron Status in Athletes: A Systematic Review, Meta-Analysis and Meta-Regression of Randomized Controlled Trials - Šmid, Anja Neža; Golja, Petra; Hadžić, Vedran; Abazović, Ensar; Drole, Kristina; Paravlic, Armin H (Sports medicine (Auckland, N.Z.), 2024)
BACKGROUND: Iron deficiency in athletes is initially treated with a nutritional intervention. If negative iron balance persists, oral iron supplementation (OIS) can be used. Despite the recent proposal for a refinement of treatment strategies for iron-deficient athletes, there is no general consensus regarding the actual efficiency, dosage, or optimal regimen of OIS. OBJECTIVE: The aim of this meta-analysis was to evaluate to what extent OIS affects blood iron parameters and physical performance in healthy adult athletes. METHODS: PubMed, Web of Science, PEDro, CINAHL, SPORTDiscus, and Cochrane were searched from inception to 2 November 2022. Articles were eligible if they satisfied the following criteria: recruited subjects were healthy, adult and physically active individuals, who used exclusively OIS, irrespective of sex and sports discipline. EXCLUSION CRITERIA: simultaneous supplementation with iron and any other micronutrient(s), intravenous iron supplementation or recent exposure to altitude acclimatisation. The methodological quality of included studies was assessed with the PEDro scale, the completeness of intervention reporting with the TIDieR scale, while the GRADE scale was used for quality of evidence synthesis. The present study was prospectively registered in PROSPERO online registry (ID: CRD42022330230). RESULTS: From 638 articles identified through the search, 13 studies (n = 449) were included in the quantitative synthesis. When compared to the control group, the results demonstrated that OIS increases serum ferritin (standardized mean difference (SMD) = 1.27, 95% CI 0.44-2.10, p = 0.006), whereas blood haemoglobin (SMD = 1.31, 95% CI - 0.29 to 2.93, p = 0.099), serum transferrin receptor concentration (SMD = - 0.74, 95% CI - 1.89 to 0.41, p = 0.133), and transferrin saturation (SMD = 0.69, 95% CI - 0.84 to 2.22, p = 0.330) remained unaltered. Following OIS, a trend of small positive effect on VO2max (SMD = 0.49, 95% CI - 0.09 to 1.07, p = 0.086) was observed in young healthy athletes. The quality of evidence for all outcomes ranged from moderate to low. CONCLUSIONS: Increase in serum ferritin concentration after OIS was evident in subjects with initial pre-supplementation serum ferritin concentration ≤ 12 µg/l, while only minimal, if any effect, was observed in subjects with higher pre-supplementation serum ferritin concentration. The doses of OIS, that induced a beneficial effect on hematological parameters differed from 16 to 100 mg of elementary iron daily, over the period between 6 and 8 weeks. Shorter supplementation protocols have been shown to be ineffective.
Keywords: železo; sportovní výkon; Anemia, Iron-Deficiency; Humans; Iron; anemie z nedostatku železa; sportovci; Ferritins; ferritiny; Hemoglobins; Administration, Oral; lidé; randomizované kontrolované studie jako téma; Athletes; Randomized Controlled Trials as Topic; potravní doplňky; Dietary Supplements; Athletic Performance; aplikace orální; hemoglobiny